AKTIVITAS LIPOLITIK Rhizopus microsporus var. rhizopodiformis ISOLAT UICC No. 6 - Iman, Iman; Sitaresmi, Sitaresmi; Prayudi, Doni; Kudin, Kudin (Makara Journal of Science, 2002)
The lipolytic activity of Rhizopus microsporus var rhizopodiformis isolat UICC No. 6. A study was carried out to examine the effect of peptone concentration (2,5% or 5%), inoculum concentration (0,1%, 0,5% or 1%) and incubation period (0 – 96 hours, interval 12 hours) on the lipolytic activity of Rhizopus microsporus var rhizopodiformis isolat UICC No. 6. Fermentation was done using the basal medium from Samad and the lipolytic activity on olive oil substrate was measured employing titration method with 0,05M NaOH. Lipolytic activity is expressed as unit/ml and one unit is defined as 1 mmol fatty acid liberated per minute. Results show that optimum lipolytic activity was obtained from 1 % inoculum, 5% peptone after 72 hours incubation period